Enhancing Vocabulary Mastery Using Audiovisual Learning Wordwall - Jayanti, Tri; Rosdiana, Alivia (Tamaddun Life, 2025)
This study examined Enhancing Vocabulary Mastery Using Audiovisual Learning Wordwall among fourth-grade elementary school students. Elementary schools faced challenges with limited instructional time for English language learning, creating a need for more efficient and engaging vocabulary teaching methods. This research used a pre-experimental design with one group taking both a pretest and posttest, including 33 fourth-grade students at SDN 1 Purwogondo. The intervention utilized Wordwall interactive audiovisual activities to teach vocabulary related to the "Be on Time" topic. Data was examined using descriptive statistics and the Wilcoxon signed-rank test. Results showed an important improvement in vocabulary mastery, with average scores increasing from 47.27 at the beginning to 81.21 at the end. The standard deviation decreased from 15.567 to 9.845, showing more consistent performance across different student ability levels. The findings suggested that Wordwall provided multiple ways for vocabulary learning, changing vocabulary study into an active, engaging process. The study added to evidence supporting technology-enhanced language learning for vocabulary development at the elementary level.